MAPPING OF CODA ATTENUATION AT THE EXTEND OF THE NATIONAL SEISMOLOGICAL NETWORK OF GREECE - Baskoutas, I.; Herraiz, M.; Perez, A. C.; Kalogeras, I.; Panopoulou, G.; Sachpazi, M.; Papadopoulos, G. (Bulletin of the Geological Society of Greece, 2004)
Coda decay rates of 538 vertical components corresponding to local earthquakes which occurred in Greece during the period 1998 to 1999 were used to deduce the coda quality factor (Qc) characteristics in the Hellenic area. The seismograms have been selected from a broader sample of 776 records obtained at 8 stations of the National Seismographic Network operated by the Institute of Geodynamics of the National Observatory of Athens. Earthquake magnitudes range from 2.5 to 4.0; epicentral distances and depths are smaller than 100 km and 40 km, respectively. Using the Single Back Scattering model, the dependence of Qc on frequencies between 1 and 10 Hz has been investigated at each station and the usual Qc =Qo f relationships have been deduced. The spatial distribution of Qo has been drawn using waves that sample approximately equivalent ellipsoidal volumes with semiminor axis up to 100 km. The corresponding map shows a decreasing trend in SN direction.